P2_1 A PREMium Model - Murgatroyd, Conan; Mott, Dan; Kinsman, Charlie; Stinton, James (Physics Special Topics, 2021)
This paper verifies that the radial density equations outlined in the Preliminary Reference Earth Model (PREM) are accurate by using them to calculate a value of 5.9728×10(24) kg for the mass of the Earth. This was found to be only 0.007% different from the known value of the Earth’s mass.